Trash talk - Herman, Hank.; Copyright Paperback Collection (Library of Congress) (New York : Bantam Books, 1996)
When the Branford Bulls' coaches go off to basketball camp, Will and Brian both want to run the show. Pretty soon the whole team is divided, and Brian and Will aren't even speaking to each other.
Keywords: Basketball -- Juvenile fiction; Basketball camps -- Juvenile fiction; Basketball stories; Young adult fiction